Utilization of Eco-print Techniques as an Environmentally Friendly Fashion Business Opportunity - Kristanti; Noor Laila Ramadhani; Purwosiwi Pandansari (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
The textile industry is one of the largest contributors to global waste, with a significant portion of this waste consisting of liquid byproducts from synthetic dyes that contain harmful chemicals. A sustainable alternative to reduce this type of waste is to replace synthetic dyes with natural dyes derived from plants. One eco-friendly dyeing method is the eco-print technique, which transfers colors and patterns directly onto fabric through contact with plant materials. This technique utilizes plant parts rich in color pigments, such as leaves, flowers, and bark. Eco-printed products have both aesthetic and market value, offering potential business opportunities. This article is based on a literature review of national and international journal sources and aims to highlight the potential of eco-printing as a profitable venture within the fashion industry.